THE CATEGORY OF SPACE AND TIME IN T.PULATOV'S NOVEL "THE TURTLE OF TARAZI" - Sergeeva, Eleonora (Журнал иностранных языков и лингвистики, 2022)
The article describes the main definitions of chronotope accepted in the scientific world and the problems raised by scholars studying the subject. The article deals with the duality of perception of space and time inherent in many works by TimurPulatov, which is based on the perception of the world through Tengriism. The study is conducted through the procedure of singling out the events that have a mythological chronotope at their core, revealing the author's worldview and contributing to the formation of a certain kind of such chronotope.